ANALISIS PENGGUNAAN BAHASA PROKEM MELALUI MEDIA SOSIAL WHATS APPLICATION (WA) PADA SISWA SMA - Aryanti, Yolanda; Indarti, Mira Dwi; Priyanto, Agus (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2019)
Prokem language is a language that is often used by adolescents, especially among high school students, which in its use often occurs in language symptoms in phonological, morphological, and semantic aspects. The purpose of this study are: 1) to describe the language of the program used by high school students, and 2) to describe the results of the analysis of the language of the aspects of language (phonology, morphology and semantics). Qualitative descriptive method is a method used by researchers in processing data. Data is collected using the observation method. All high school students were used by researchers as a population and 25 students as samples. The results showed: 1) high school students still use professional language when communicating with adults through WhatsApp social media, 2) based on the results of analysis from phonological aspects, students often change certain fonts, such as phonemes / a / phonemes / e /, phoneme additions , as well as the use of regional languages, 3) based on morphological aspects, there are uses of affixes derived from Sundanese, and 4) based on semantic aspects, students often use acronyms derived from English as well as prokem from Javanese and Arabic.